(untitled) (UNED Research Journal, 2024)
Introduction: Shade coffee farms are complex ecosystems and there is a need for better understanding of their function and environmental services. Some of their environmental functions are similar to forest ecosystems and biodiversity is important. Mammals play a crucial role in these agroecosystems, controlling vegetation abundance and composition, contributing to seed dispersal, nutrient recycling and soil maintenance through excavation and aeration. Objective: To identify the role of wild mammals in seed dispersal and food chain in Costa Rican coffee agroecosystems. Methods: We worked in Rincón de Mora, San Ramón, Costa Rica, from March 2019 to January 2022. We used Pixestt and Havahart traps, and camera traps, to examine feces and behavior; depending on species, sample size ranged between 2 and 87. Results: We identified 19 species of mammals. Heteromys salvini had coffee beans in its pockets. Echinosciurus variegatoides, Didelphis marsupialis and Philander melanurus fed on the local vegetation. Dasyprocta punctata had the most diet data; we found a beetle in the feces of Procyon lotor and observed Eira barbara chasing D. punctata. Conclusion: Coffee agroecosystems provide food for wild mammals, which in turn contribute to the coffee ecosystem as seed dispersers and population control.